Efeitos da deficiência de tiamina em camundongos adultos sobre parâmetros eletrofisiológicos e morfológicos das células de Purkinje cerebelares - Ivonne Carolina Bolanos Burgos (2019)
Thiamine (vitamin B1) is an essential vitamin that plays an important role in many enzymatic processes involved in brain function. Thiamine acts through its phosphorylated forms, thiamine monophosphate, thiamine diphosphate and thiamine triphosphate, that contribute to cellular functions including carbohydrate metabolism, synthesis of neurotransmitters such as acetylcholine, membrane conductance and synaptic transmission. Thiamine deficiency in the central nervous system causes changes in cellular metabolism that may lead to neuronal dysfunction or death. The cerebellum, especially the anterior vermis, is one of the brain regions most affected by thiamine deficiency, which affects the morphology and function of cerebellar Purkinje cells that form the only efferent pathway from this region. Changes in the function of Purkinje cells are related to the development of cerebellar ataxia, which is one of the clinical signs of Wernicke-Korsakoff syndrome, a neurodegenerative disease associated with thiamine deficiency. However, little is known about the effects of thiamine deficiency on the electrophysiological and morphological properties of Purkinje cells. The objective of this work was to evaluate the effects of thiamine deficiency in adult mice on electrophysiological and morphological parameters of Purkinje cells in slices of the cerebellar vermis in vitro. We used a model of thiamine deficiency based on diet (thiamine free chow) and daily injects of pyrithiamine, an inhibitor of thiamine diphosphate (deficient groups) or thiamine (control groups) for 13 days of treatment. The treatment was applied in C57 / Black mice, male, adult (8 weeks), 20-25 g body mass, which were distributed in 4 experimental groups: 1) Control 2) Deficient, 3) Control recovered and 4) Deficient recovered. The animals were submitted to electrophysiological and morphological studies in one of two stages: 1) when the deficient group presented clinical signs of thiamine deficiency or 2) after recovery following a single application of thiamine, followed by water and standard chow ad libitum for 7 days. Morphological studies were performed in the first stage. Electrophysiological studies were performed on Purkinje cells of the cerebellar vermis using the Whole-cell current clamp technique. Spontaneous activity and responses to current injection protocols were recorded to determine the reobase, input resistance and the relationship between the injected current and the frequency of action potentials. For morphometric analysis, the number of Purkinje cells, their largest diameter and smallest diameter and the diameter of their nucleus were analyzed. We did not detect any significant difference between groups in the number or density of Purkinje cells. However, measurements of cell diameters revealed a modest (7%) but statistically significant reduction in the size of Purkinje cell soma, principally along its minor axis, in thiamine deficient animals. The size of the nucleus was also reduced proportionally. The observed reduction in size was not, however, sufficient to alter membrane input resistance, as this parameter was not different between groups. The frequency of spontaneous action potentials and the relationship between action potential firing rate and current injection were also not significantly different between groups. However, reobase was strongly (55%) reduced in thiamine deficient animals compared to control or to recovered groups. We conclude that thiamine deficiency changes the electrophysiology properties of Purkinje neurons without causing marked morphological alterations